THE EFFECT OF FREE DRAWING ABILITY AND EMOTIONAL INTELLIGENCE ON THE DEVELOPMENT OF CREATIVITY FOR CHILDREN AGED 5-6 YEARS IN EARLY CHILDHOOD EDUCATION MARTABE KASIH, SILIMABAHAL VILLAGE, SIBORONGBORONG DISTRICT - Sartika Sareany Tambunan; Syamsu Nahar; Wahyudin Nur Nasution (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2022)
This study aims to determine (1) free drawing activities have a significant influence on children's creativity, (2) emotional intelligence has a significant influence on children's creativity, and (3) the interaction between free drawing activities and emotional intelligence has an influence on children's creativity. The research method used in this study is a quasi-experimental method with a 2x2 factorial design. The study population was all children of PAUD Martabe Kasih, Silimabahal Village, Siborongborong District aged 5-6 years, consisting of 2 classes totaling 48 children. The sample of this study was for the control group, namely the children of group B1 which amounted to 24 children, while the experimental group, namely the children of group B2, which amounted to 24 children. The results of this study are (1) there is a positive and significant effect of free drawing activities on children's creativity, this is evident from Fcount 133.87 > Ftable 3.972. In this case, the average results of the creativity test of children who are taught with free drawing activities are higher than those of drawing activities with teacher instructions, so it can be concluded that free drawing activities are more effectively applied in learning to increase children's creativity. (2) there is a positive and significant effect of emotional intelligence on children's creativity, this is evident from Fcount 6.03 > Ftable 3.972. In this case, the average results of creativity tests for children with high emotional intelligence as a whole, both those taught with free drawing activities and drawing with teacher instructions, are higher than the average results of creativity tests for children with low emotional intelligence, and (3) there is an interaction of free drawing activities and emotional intelligence that have an influence on children's creativity, this is evident from Fcount 7.09 > Ftable 3.972. In this case, the average creativity test results of children with high emotional intelligence are better taught using free drawing activities compared to using drawing activities with teacher instructions, while children with low emotional intelligence are better taught using drawing activities with teacher instructions compared to children with low emotional intelligence. free drawing activity.